Examining the Effect of Work Discipline on Employee Performance with Work Motivation as a Mediating Variable: Evidence from the Biak Numfor Police - Denny Ari Pratama; Arthur Sitaniapessy; Albert Gamot Malau (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the influence of work discipline on the performance of personnel at Biak Numfor Police Resort, with work motivation as an intervening variable. The research is motivated by the high rate of disciplinary violations within the Biak Numfor Police, which has led to a decline in performance and professionalism among personnel. A quantitative approach was applied using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method. The sample consisted of 220 active police officers selected through purposive sampling, while the research instrument was developed based on validated and reliable indicators. The results indicate that work discipline has a positive and significant effect on both work motivation and performance. Furthermore, work motivation has a significant influence on performance and mediates the relationship between work discipline and performance. These findings emphasize that work discipline not only directly contributes to improved performance but also builds internal motivation that drives more optimal results. This research provides practical implications for police leadership, particularly the need to implement consistent disciplinary policies, foster a positive work culture, and develop reward systems that enhance motivation. Such strategies are expected to strengthen discipline, boost internal motivation, and ultimately optimize personnel performance at the Biak Numfor Police Resort.